Formulasi Sediaan Gel Sari Buah Duwet (Syzygium cumini) dengan Basis Karbopol 940 Sebagai Gelling Agent - Yohanes Juliantoni; Wahida Hajrin; Windah Anugrah Subaidah (Sasambo Journal of Pharmacy, 2020)
Duwet fruit (Syzygium cumini) is a local Indonesian fruit that has many benefits. Duwet juice contains antioxidants that have DPPH free radical activity. But the use of duwet fruit is not practical for modern society. This research was conducted to formulate duwet juice into a gel-based carbopol 940 with the physical quality test of the gel. Duwet fruit extraction was tested for phytochemical screening qualitatively. The gel is made in 5 formulas namely I (100% aquadest: 0% ethanol 70%); II (75% aquadest: 25% ethanol 70%); III (50% aquadest: 50% ethanol 70%); IV (25% aquadest: 75% ethanol 70%); and V (0% aquadest: 100% ethanol 70%). The results showed that Duwet juice contained of flavonoid, polyphenols, and anthocyanins based on phytochemical screening tests. The formula of gel I, II, and III has fulfilled the pH requirements of 4.5-6.5, homogeneity, and spread capacity of 5-7 cm. Increasing the concentration of 70% ethanol in the gel formula will increase the pH value and spread capacity.